Ageing and quenching through the ageing diagram: predictions from simulations and observational constraints. Issue 1 (16th January 2023) - Corcho-Caballero, Pablo; Ascasibar, Yago; Sánchez, Sebastián F; López-Sánchez, Ángel R
ABSTRACT: We study recent changes on the star-formation history (SFH) of galaxies by means of the ageing diagram (AD), tracing the fraction of stars formed during the last ∼20 Myr through the equivalent width of the $\rm Hα$ line and ∼1−3 Gyr through the dust-corrected optical colour ( g − r )0 or the Balmer break. We provide a physical characterization by using Pipe3D estimates of the SFH of Calar Alto Legacy Integral Field Area and Mapping Nearby Galaxies at Apache Point Observatory galaxies, in combination with the predictions from IllustrisTNG-100. Our results show that the AD may be divided into four domains that correlate with the stellar mass fractions formed in the last 20 Myr and 3 Gyr: ageing systems, whose star formation rate changes on scales of several Gyr, account for $70-80{{\ \rm per\ cent}}$ of the galaxy population. Objects whose SFH was abruptly truncated in the last ∼1 Gyr arrange along a detached quenched sequence that represents $\sim 5-10{{\ \rm per\ cent}}$ by (volume-corrected) number for 10 9 < M * /M⊙ < 10 12 . Undetermined systems represent an intermediate population between the ageing and quenched regimes. Finally, Retired galaxies, dominated by old stellar populations, are located at the region in the AD where the ageing and quenched sequences converge. Defining different star formation activity levels in terms of the birth rate parameter $b\equiv \frac{SFR}{\langle SFR \rangle }$, we find that galaxies transit from the ageing to quenched sequences on scales ∼500 Myr. We conclude that the AD provides a useful tool to discern recently quenched galaxies from the dominant ageing population.